European and American banking sector in 2004–2012 (Economic and Political Thought, 2014)
The financial crisis has had a significant influence on the European andthe US banking sector. The results of the analysis show that as a result ofthe crisis the size of the banking component of the most developed financialsystems has decreased. At the same time, cross-border expansion has lostits importance. The concentration level has ceased to rise in the EuropeanUnion, and economic efficiency is subject to significant volatility. In thiscontext, it should be noted that the process of creating a single market forfinancial services is far from being completed in the European Union. Theevolu tion of the US banking sector bears some similarity to the performanceof the European banks, however credit institutions in the US have betterfinancial results.